DEVELOPMENT OF THE LEARNING TOOLS OF BIOLOGY TEACHING MATERIAL WASTE MANAGEMENT ORIENTED ENTREPRENEURSHIP - Prasetiyo .; Sumarno . (Universitas PGRI Semarang, 2011)
ABSTRACT Waste management material on the subjects of biology can be used to enhance the values ?óÔé¼ÔÇ??óÔé¼ÔÇ?of entrepreneurship for students. Therefore, we need to develop relevant learning tools. The purpose of this research is to develop entrepreneurship-oriented learning tool which is effective to increase the values ?óÔé¼ÔÇ??óÔé¼ÔÇ?of students entrepreneurship. The study was conducted in SMA 11 Semarang (Semarang 11 th high school) with the subject of tenth grade students of the 2010/2011 school year. The type of research is the research and development (R & D). This research is used to produce certain products, as well as test the effectiveness of these products. Product to be produced is the learning tools of biology that include: instructional materials, lesson plans, syllabi and worksheets. The result showed that the resulting product has validity value of (Va.) = 4. The average score for syllabi, lesson plans, teaching materials and worksheets is = 4. In addition, the entrepreneurship learning interest of students in entrepreneurship-oriented waste management learning have increased 8.2% for ordinary regular classes and 6.4% for the excellent class. The conclusion is, the entrepreneurial-oriented learning tool developed is effective way to increase entrepreneurship interest in learning biology. Key words: waste, entrepreneurship, learning tools